2018
DOI: 10.3390/v10100542
|View full text |Cite
|
Sign up to set email alerts
|

The Westward Journey of Alfalfa Leaf Curl Virus

Abstract: Alfalfa leaf curl virus (ALCV), which causes severe disease symptoms in alfalfa (Medicago sativa L.) and is transmitted by the widespread aphid species, Aphis craccivora Koch, has been found throughout the Mediterranean basin as well as in Iran and Argentina. Here we reconstruct the evolutionary history of ALCV and attempt to determine whether the recent discovery and widespread detection of ALCV is attributable either to past diagnostic biases or to the emergence and global spread of the virus over the past f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
3
3
0
Order By: Relevance
“…The results suggested that ALCV isolates in China originated from a single ALCV isolate similar to what has been reported for ALCV in Argentina (Davoodi et al, 2018). These authors also suggested that the virus most likely originated in Iran (Davoodi et al, 2018). For PeSV and ADV, there was significant variation between the isolates from China and those from other countries (Figures 9B,H).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results suggested that ALCV isolates in China originated from a single ALCV isolate similar to what has been reported for ALCV in Argentina (Davoodi et al, 2018). These authors also suggested that the virus most likely originated in Iran (Davoodi et al, 2018). For PeSV and ADV, there was significant variation between the isolates from China and those from other countries (Figures 9B,H).…”
Section: Discussionsupporting
confidence: 78%
“…ALCV sequences from the 4 surveyed provinces were highly conserved ( Figures 11B,C ) and most closely related to the isolates from Argentina ( Figure 11A ), but a significant variation to the isolates from other countries ( Figures 11B,C ). The results suggested that ALCV isolates in China originated from a single ALCV isolate similar to what has been reported for ALCV in Argentina ( Davoodi et al, 2018 ). These authors also suggested that the virus most likely originated in Iran ( Davoodi et al, 2018 ).…”
Section: Discussionsupporting
confidence: 78%
“…ALCV isolates were found to be highly recombinogenic and it was suggested that recombination has been a determining factor in the origin of the different viral genotypes. The ALCV sequence data support the hypothesis that the virus likely emerged and diversified in the Middle East before spreading to the western Mediterranean basin and Argentina ( Davoodi et al, 2018 ). The international research conducted on ALCV is a good example highlighting the need to combine the power of HTS for the detection and identification of poorly known viruses with the reliability of classical molecular methodology to obtain complete genomes of novel viruses and understand their evolution ( Bernardo et al, 2016 ).…”
Section: Alfalfa Virome: Recent Developmentssupporting
confidence: 75%
“…More recently, the siRNA-based HTS of alfalfa samples displaying symptoms of dwarfism disease in Argentina and symptoms of dwarfism, shrinkage and mottle mosaic in China resulted in the identification of novel ALCV isolates ( Bejerman et al, 2018 ; Guo et al, 2019 ) belonging to ALCV genotype D, which is divergent from three other genotypes (A, B, and C) found in many European countries, Northern Africa and the Middle East ( Davoodi et al, 2018 ). Thus far, one hundred and twenty complete ALCV genome sequences have been recovered from ten countries, and four ALCV genotypes (ALCV-A, ALCV-B, ALCV-C, and ALCV-D) have been clearly distinguished ( Davoodi et al, 2018 ). The identification of these isolates expanded the known geographical range of ALCV and shed more light on the distribution of this emergent alfalfa virus.…”
Section: Alfalfa Virome: Recent Developmentsmentioning
confidence: 99%
“…Alfalfa mosaic virus (AMV) is the most widespread virus that highly impacts alfalfa yield worldwide [ 14 ]. The recently discovered alfalfa leaf curl virus (ALCV) is also causing a severe disease of global distribution and impact [ 20 ]. Cucumber mosaic virus (CMV), lucerne transient streak virus (LTSV), lucerne Australian latent virus (LALV), bean leafroll virus (BLRV), beet western yellows virus (BWYV), soybean dwarf virus (SbDV), and turnip yellows virus (TYV) are also of potential impact for alfalfa [ 14 , 16 , 17 ].…”
Section: Viruses Infecting Major Legumesmentioning
confidence: 99%